A cell culture device equipped with a micro-needle electrode array fabricated using backside exposure mold and resin casting. - Hatsuzawa, Takeshi; Kurosaka, Mikiya (Biomedical Microdevices, 2018)
A cell culture device equipped with a micro-needle electrode array was fabricated for the signal analysis of cell spheroids, cell masses, and cell sheets. For the analysis, sharp needle electrodes with a high aspect ratio for facilitating easy penetration into the cell mass and a small pitch for fine spatial resolution were required. Microelectromechanical systems (MEMS) technology is one of the common solutions for the fabrication of devices. However, an additional process, such as anisotropic etching or electro-polishing, is required for fabricating sharp needles. Tapered needles were fabricated using backside exposure for coating a layer of thick resist film on a glass substrate. The incident beam from mask apertures were diffracted and attenuated in the medium, resulting in tapered intensity distribution. A needle-like shape was obtained after performing resist development without using additional MEMS process. In this study, the theoretical analysis of optical intensity distribution and design and fabrication process of the device were described. Finally, the effectiveness of the device was evaluated by adding cultured cell mass on the needle array. Signals with spikes and fluctuations were observed in the electrode covered with cell mass, whereas only noise was observed on the non-covered electrode, demonstrating the signal pick-up ability of the device during cell culture.